Cooperative feeding in common dolphins as suggested by ontogenetic patterns in δ15N bulk and amino acids. Issue 6 (5th May 2021) - Ruiz‐Cooley, Rocio I.; Gerrodette, Tim; Chivers, Susan J.; Danil, Kerri
Abstract: Understanding the effect of stage‐specific traits on species feeding habits can reveal how natural selection shapes life strategies. Amino acid (AA) nitrogen stable isotopes (δ 15 N) provide multiple proxies of habitat baseline values and diet that can improve our understanding of species feeding strategies relative to their animal metabolism. We evaluated the effect of body length as a proxy for life stage and sex on the feeding habits of the common dolphin Delphinus delphis delphis using δ 13 C and δ 15 N in bulk tissue and AAs δ 15 N from skin samples collected for almost two decades. For bulk δ 13 C and δ 15 N data, we used SIBER analysis to compare isotopic niches by sex and life stage. For AA δ 15 N data, we developed a hierarchical Bayesian model (HBM) to estimate indices of trophic status (Δ 15 N and trophic position). The model reflected the natural hierarchical structure of AA data by partitioning variability into three sources: between laboratory replicates, within dolphins and among dolphins. Estimates of Δ 15 N based on all trophic and source AAs were more precise for each dolphin, less variable among dolphins and on average 2.4‰ higher than indices based on single trophic (Glx) and source (Phe) AAs. Precision was further increased when information was shared among individuals through random effects or regression models. Estimates of trophic position showed similar patterns. Both Δ 15 N and δ 15 Nbulk isotopic niches showed no difference by sex, suggesting that males and females have similar feeding habits and may not segregate. However, lower Δ 15 N values for weaning calves and smaller juveniles discriminate them from adults, whereas δ 15 N bulk isotopic niches do not. A trophic discrimination factor (TDFTro‐Src ) of 3.1‰ was required for reasonable estimates of trophic position for these dolphins. Together, the lack of δ 15 N differences between sexes, low variation between juveniles and adults and knowledge of common dolphins' social organization support intraspecific feeding cooperation as an important strategy to feed in the highly dynamic marine environment. Our study also presents an efficient way to analyse complex AA δ 15 N data using HBM to investigate foraging behaviour in long‐lived marine species difficult to study in the wild. Abstract : Our long‐term study provides insights about the ontogeny of common dolphin feeding strategies using δ 13 C and δ 15 N values from skin, and amino acid δ 15 N values analyzed with Bayesian statistics. The latter included development of a hierarchical Bayesian model for analyses of complex amino acid δ 15 N data. Photo: NOAA Fisheries, SWFSC under permit 774‐1714‐10.